1992
DOI: 10.1021/bi00156a009
|View full text |Cite
|
Sign up to set email alerts
|

Novel .alpha.- and .omega.-conotoxins and Conus striatus venom

Abstract: Three neurotoxic peptides from the venom of Conus striatus have been purified, biochemically characterized, and chemically synthesized. One of these, an acetylcholine receptor blocker designated alpha-conotoxin SII, has the sequence GCCCNPACGPNYGCGTSCS. In contrast to all other alpha-conotoxins, SII has three disulfide bonds (instead of two), has no net positive charge, and has a free C-terminus. The other two paralytic peptides are Ca channel-targeted omega-conotoxins, SVIA and SVIB. omega-SVIA is the smalles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 24 publications
(23 reference statements)
1
84
1
Order By: Relevance
“…These IV samples contained peptides that were previously characterized from the DV of this species, including the calcium-channel blocker ω-SVIA (Ramilo et al, 1992) and nicotinic acetylcholinereceptor blockers α-SI and α-SII (Ramilo et al, 1992;Zafaralla et al, 1988), as confirmed by MALDI-MS. Interestingly, neither s4a nor s4b were observed components of the IV from these snails.…”
Section: Variation In the Composition Of Injected Venom Inmentioning
confidence: 92%
See 2 more Smart Citations
“…These IV samples contained peptides that were previously characterized from the DV of this species, including the calcium-channel blocker ω-SVIA (Ramilo et al, 1992) and nicotinic acetylcholinereceptor blockers α-SI and α-SII (Ramilo et al, 1992;Zafaralla et al, 1988), as confirmed by MALDI-MS. Interestingly, neither s4a nor s4b were observed components of the IV from these snails.…”
Section: Variation In the Composition Of Injected Venom Inmentioning
confidence: 92%
“…It is apparent both by the number of peaks that appear in the chromatograms, and the masses labeled, that IV is by no means identical to DV and contains a small subset of DV peptides, primarily less hydrophobic ones. Identifiable DV and IV peptides were fully processed from their propeptides and contained the known post-translational modifications such as carboxy-terminal amidation (s4a, ω-SVIB and α-SI) and proline hydroxylation (s4a and ω-SVIA; Craig et al, 1998;Ramilo et al, 1992;Zafaralla et al, 1988). Peptides s4a and s4b were also modified by O-glycosylation and pyroglutamylation (Craig et al, 1998).…”
Section: Comparison Of Duct Venom and Injected Venom Samples Inmentioning
confidence: 99%
See 1 more Smart Citation
“…co-CmTxa was synthesized on a re-plumbed ABI Model 430A peptide synthesizer, using standard t-BOC chemistry with some modifications [14] in the manner previously described [15,16]. Synthetic preparations were subjected to amino acid analyses [16] and the results were consistent with the expected amino acid composition (data not shown). The authenticity of the synthetic o)-conotoxins were also confirmed by comparison to the purified, native peptides (kindly provided by Dr. B. Olivera) using a variety of chemical and biological methods.…”
Section: Sample Preparationmentioning
confidence: 96%
“…1 The majority of ␣-conotoxins isolated from fishhunting cone snails, including GI, GIA, and GII from Conus geographus (4), MI from Conus magus (5), and SI and SII from Conus striatus (6,7), show extensive structural homology, a conserved cysteine framework, and target the muscle subtype of the nAChR. The ␣-conotoxins PnIA and PnIB from a molluschunting cone snail, Conus pennaceus (8), and ImI from a wormhunting cone snail, Conus imperialis (9) share a similar cysteine framework to ␣-conotoxins from fish-hunting cones, but have a different sequence pattern and target the neuronal subtypes of the nAChR.…”
mentioning
confidence: 99%